Reaction of potassium phosphide KP(iPr)Ter with chalcogens, heteroallenes and an acyl chloride. Issue 45 (5th November 2021) - Szych, Lilian Sophie; Lüdtke, Karsten Paul; Pilopp, Yannic; Bresien, Jonas; Villinger, Alexander; Schulz, Axel
Abstract : Investigations on the reactivity of phosphide KP( i Pr)R 1 toward chalcogens, heteroallenes and an acyl chloride are reported, revealing the distinct nucleophilicity of the potassium phosphide. Abstract : The reactivity of the secondary phosphide KP( i Pr)Ter (1 ) (Ter = 2, 6-bis-(2, 4, 6-trimethylphenyl)phenyl) toward small molecules is reported. Phosphide 1 displays distinct nucleophilic character and reacts selectively with chalcogens (S8, Se x ), heteroallenes (CO2, n PrNCS), and an acyl chloride (AdCOCl) to give the corresponding dichalcogenophosphinates (2a, 3 ), phosphanyl formate (5 ), thiocarbamoylphosphane (6a ), or acylphosphane (7a ), respectively. Furthermore the follow-up chemistry of these products was investigated. 2a was converted to a PSPS ligand (2b ) which forms a Au(i ) complex (2c ) with (Me2 S)AuCl. Likewise, a gold complex of 7a was prepared. All species were isolated and fully characterized.